Study of Physics Using Mental Experiments (Texas Journal of Multidisciplinary Studies, 2022)
The article discusses the forms of development of students' thinking skills, types of intellectual experimental-theoretical thinking, external illustrative mental experiments, the ability to more visually describe the conclusions of physical theory, the degree of study of the studied process or physical phenomenon in a mental experiment.